Neural stem cell-derived extracellular vesicles favour neuronal differentiation and plasticity under stress conditions - Ocaña, Susana Delgado; Magaquian, Dario; Banchio, Claudia (Frontiers in Molecular Neuroscience, 2023)
Extracellular vesicles (EVs) are released by all cell types and are involved in intercellular communication. We evaluated if neural stem cells-derived EVs (NSC-EVs) regulate NSCs proliferation and differentiation under control and stress conditions. We found that NSC-EVs treatment increases cell proliferation and promotes neuronal differentiation and plasticity. The fact that nervous tissue poorly recovers after cellular damage, prump us to evaluate the effect of EVs supplementation under oxidative stress and inflammation. We demonstrate that NSC-EVs restore the proliferative potential of the NSCs affected by oxidative stress. In addition, we provide evidence that oxidative stress and inflammation induce neuronal differentiation. Interestingly, the aberrant cell phenotype induced by inflammation is restored by NSC-EVs treatment, suggesting that these vesicles ameliorate the damage burden in neurons and modulate neuronal plasticity. These results contribute to understand the role of the NSCs-derived EVs as key players for brain tissue generation and regeneration and open new pathways to the development of therapies.